Pengembangan Media Pembelajaran Permainan Monopoli Berbantuan Barcode pada Materi Geografi di Kelas XI - Wulan Sriyana; Rendra Zainal Maliki; Amalia Novarita; Ika Listiqowati (Jurnal Penelitian Pendidikan Geografi, 2025)
Learning is an activity carried out by students actively and independently, supported by a well-prepared environment to enhance learning readiness. Learning media refers to various objects, whether tools, materials, or conditions, that function as communication intermediaries during the learning process. Developing a monopoly game-based learning tool by utilizing advanced technology can increase variety and engagement in learning. This study aims to develop a barcode-assisted monopoly learning media that is valid for Geography subject in Grade XI of SMA Negeri 4 Sigi. The research method employed was Research and Development (R&D). The results show that the developed media obtained an expert validation score of 97.22%, categorized as highly valid, and a small group trial involving 21 students resulted in a validity percentage of 91.56%, also categorized as highly valid. Therefore, the barcode-assisted monopoly learning media is feasible to be used as an innovative geography learning tool and has the potential to enhance students’ learning enthusiasm. The implication of this study highlights that integrating technology-based educational games can improve learning effectiveness, foster student motivation, and provide adaptive and contextual media alternatives to support the achievement of core competencies in secondary schools.